GAMBARAN PENGETAHUAN IBU HAMIL DALAM MENGKONSUMSI TABLET FE DI PUSKESMAS BANIONA KECAMATAN WOTAN ULUMADO KABUPATEN FLORES TIMUR - Apolonia Ratna Deran Rotok; Maria Yasintha Goa; Yasinta Betan (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2022)
Iron supplementation is an important effort in preventing and overcoming anemia, and is the most effective way, because it contains folic acid. Therefore, it is very important for pregnant women to consume FE tablets regularly. Compliance with pregnant women in consuming FE is a health behavior that is influenced by various factors, one of which is knowledge. This study aims to describe the knowledge of pregnant women in consuming Fe tablets at the Baniona Health Center, Wotan Ulumado District, East Flores Regency. The research design used was descriptive quantitative with cross sectional approach. The research samples were all pregnant women who had their pregnancy checked in the working area of ​​the Baniona Community Health Center and had met the inclusion criteria, namely: 1. Pregnant women who performed the examination in the Baniona Community Health Center working area; 2. Willing to be a respondent; and 3. Pregnant women who can read and write. The number of respondents as much 152 pregnant women and the study was conducted in January 2021. The sample was selected using a total sampling technique. Data were collected using a questionnaire. Data analysis using univariate anilysis. The results showed that the knowledge of pregnant women was obtained by 60 respondents (39.5%) with a low level of knowledge and 92 respondents (60.5%) with a good level of knowledge. Conclusion: the majority of pregnant women consuming FE at Baniona Health Center are in good category. Keywords: Knowledge, Pregnant Women, Fe Tablets